Design of an electronic device in the STEAM context to relate results of physical measurements with sounds, and its analysis through science teachers’ perception - Perea Martins, João E. M. [UNESP] (Universidad Pablo de Olavide, 2024)
This work presents the design and details of an electronic system that uses software and hardware aspects to generate sound frequencies associated with the measurement of physical phenomena, such as temperature or other. It has potential to create fun and motivation activities in the classroom, encouraging the students to think about the association between scientific and technological aspects. It is based on a STEAM (Science, Technology, Engineering, Arts, and Mathematics) approach where an Arduino processing board measures a physical phenomenon value with a sensor, computes a mathematical relationship to define an associated sound frequency, and next sends an output signal to excite a speaker. The proposed electronic system is simple, but this subject may not be very familiar to many science teachers and, therefore, this article explains it step by step to allow its effective understanding and later usage in the classroom. Furthermore, this article also presents a discussion with science teachers in order to analyze their perception when they are challenged to understand and analyze the proposed system under a teaching perspective, which emphasized concernments such as the lack of training and materials, but positively indicates the proposal is feasible and has a satisfactory teaching potential.
Proyecto de un dispositivo electrónico en el contexto STEAM para relacionar resultados de mediciones físicas con sonidos, y su análisis a través de la percepción de profesores de Ciencias
Keywords: Arduino; Digital skills; Educational technology; Mathematical relationships; Sensors; STEAM; Teachers training; Technology